WAGNER VERSUS MOZART IN THE UKRAINIAN THEATRE (Security Dialogues, 2023)
Privatisation and outsourcing of war have become a feature of contemporary armedconflicts. It is also true for the conflict in Ukraine; the participation of many private militaryactors has been recorded, of which Mozart and Wagner groups - often called ‘orchestra’ aswell as International Legion of Defence of Ukraine stand out in the Ukraine theatre. On theone hand, private military actors taking part in the conflict on the Ukrainian side are calledvolunteers, while private military actors participating on the Russian side are designatedas mercenaries. Therefore, the question can be asked: ‘What is the difference betweenprivate military actors participating in the Ukrainian battlefield and how are they treatedlegally?’ In order to answer the asked question, the paper started from the basic definitionsof private military actors and relevant legal regulations, and then the most important actorsparticipating in the Ukrainian battlefield were presented, as well as their legal treatment. It isconcluded that due to the lack of a binding international regulation in this area, lots of privateactors operate in a legal vacuum and that their determination is rather a matter of politicsthan of law. Therefore, the difference between these actors is the narrative and sentimentthat describes them and justifies their engagement.
Keywords: private military companies, mercenaries, volunteers, Wagner Group, Mozart Group, International Legion of Defence of Ukraine